Primary immunodeficiency diseases in Latin America: proceedings of the Second Latin American Society for Immunodeficiencies (LASID) Advisory Board (2011)
ABSTRACT: Early diagnosis and appropriate therapy are essential for the best prognosis and quality of life in patients with primary immunodeficiency diseases (PIDDs). Experts from several Latin American countries have been meeting on a regular basis as part of an ongoing effort to improve the diagnosis and treatment of PIDD in this region. Three programmes are in development that will expand education and training and improve access to testing facilities throughout Latin America. These programmes are: an educational outreach programme (The L-Project); an immunology fellowship programme; and the establishment of a laboratory network to expand access to testing facilities. This report provides the status of these programmes based on the most recent discussions and describes the next steps toward full implementation of these programmes.